Identification of CO2 leakage from geological storage based on maize spectral characteristic indexes. (December 2021) - Xue, Lu; Ma, Junjie; Hu, Qian; Cheng, Meng; Wen, Xiaoyu; Wu, Ning; Liu, Dan; Zhao, Chenyang; Ma, Jinfeng
Highlights: Biological characteristics and single spectral parameters of maize have problems of sensitivity and rapidity in the identification of CO2 leakage. The three spectral characteristic indexes of REP-BEP, RGP/RRV and RGP-RRV/RGP+RRV are capable of identify CO2 leakage. The three spectral characteristic indexes of RVP-GPP, REP-BEP and MCARI can be used for quantitative inversion of soil CO2 concentration. The REP-BEP index can simultaneously identify CO2 leakage and quantitatively invert the soil CO2 concentration. Abstract: CO2 capture and storage (CCS) is an important technical strategy to reduce global CO2 emission from heavy industries. However, the risk of CO2 leakage in CCS-related projects cannot be ignored and it is crucial to identify and monitor CO2 leakage in CCS project areas in a timely and effective manner. So here we investigate the biological characteristics (plant height, leaf length, leaf width and SPAD value) and leaf spectral characteristics of maize under soil CO2 concentration of 10, 30, and 50%, with normal soil condition as control (CK). By analysing the original spectrum and first derivative spectrum of maize leaves, spectral parameters relatively sensitive to soil CO2 stress were extracted. Further, eight composite spectral characteristic indexes that are expected to identify CO2 leakages were constructed and analyzed. Besides, the normalized pigment chlorophyll index (NPCI) and modified chlorophyll absorption in reflectance index (MCARI) were also investigated for the indication role in CO2 leakage. The results showed that maize morphological traits had a significant hysteresis effect for the indication of CO2 leakage; the SPAD value was difficult to indicate the lower concentration of soil CO2 early. But it was found that three spectral characteristic indexes REP-BEP, RGP/RRV and RGP-RRV/RGP+RRV can effectively identify CO2 leakage, and three spectral characteristic indexes (RVP-GPP, REP-BEP and MCARI) can be used for quantitative inversion of soil CO2 concentration. Especially, REP-BEP index could both indicate CO2 leakage and quantitatively inverse soil CO2 concentration. In sum, the spectral characteristic indexes of maize leaves can be used as effective indicators to quickly and effectively identify CO2 leakage and quantitatively invert the CO2 concentration in soil.